Answer:
Option (d) is correct.
The factored form of given quadratic equation
is ![(3x-1)(x+8)](https://tex.z-dn.net/?f=%283x-1%29%28x%2B8%29)
Step-by-step explanation:
Given :equation ![3x^2+23x-8](https://tex.z-dn.net/?f=3x%5E2%2B23x-8)
We have to factorize the given quadratic equation.
Consider the given quadratic equation ![3x^2+23x-8](https://tex.z-dn.net/?f=3x%5E2%2B23x-8)
we can factorize the given quadratic equation using middle term splitting method,
split middle term in such a way that the middle term becomes the product of two other terms.
23x can be written as 24x-x
equation becomes,
![3x^2+23x-8](https://tex.z-dn.net/?f=3x%5E2%2B23x-8)
![\Rightarrow 3x^2+24x-x-8](https://tex.z-dn.net/?f=%5CRightarrow%203x%5E2%2B24x-x-8)
Taking 3x common from first two terms and -1 common from last two terms , we get,
![\Rightarrow 3x(x+8)-1(x+8)](https://tex.z-dn.net/?f=%5CRightarrow%203x%28x%2B8%29-1%28x%2B8%29)
![\Rightarrow (3x-1)(x+8)](https://tex.z-dn.net/?f=%5CRightarrow%20%283x-1%29%28x%2B8%29)
Thus, The factored form of given quadratic equation
is ![(3x-1)(x+8)](https://tex.z-dn.net/?f=%283x-1%29%28x%2B8%29)